Odpowiedzi

Najlepsza Odpowiedź!
2010-03-02T21:41:14+01:00
6(x-4)-2=6x-24-2=6x-26
2(x+1)-3(x-1)=2x+2-3x+3=-x+5
-3(y-2)+4(y+2)=-3y+6+4y+8=y+14
5(x-y-1)-4(x+2)=5x-5y-5-4x-8=x-5y-13
2(3a+b)-2(a-b)=6a+2b-2a+2b=4a+4b
½(4x-4)-2x=2x-2-2x=-2
x(x-1)-3(x²-1)=x²-x-3x²+3=-2x²-x+3
5a(a-3)-3a(a-5)=5a²-15a-3a²+15a=2a²
3x(x+⅓y)-2y(½x-½)=3x²+xy-xy+y=3x²+y
2010-03-02T22:00:08+01:00
6(x-4)-2=6x-24-2=6x-26
2(x+1)-3(x-1)=2x+2-3x+3=-x+5
-3(y-2)+4(y+2)=-3y+6+4y+8=y+14
5(x-y-1)-4(x+2)=5x-5y-5-4x-8=x-5y-13
2(3a+b)-2(a-b)=6a+2b-2a+2b=4a+4b
½(4x-4)-2x=2x-2-2x=2
×(×-1)-3(ײ-x)=x²-x-3x²-3x=-2x²-4x
5a(a-3)-3a(a-5)=5a²-15a-3a²+15a=2a²
3x(x+⅓y)-2y(½x-½)=3x²+xy-xy-y=3x²+y